Alginate is not a significant component of the extracellular polysaccharide matrix of PA14 and PAO1 Pseudomonas aeruginosa biofilms - Wozniak, Daniel J. (National Academy of Sciences, 2003)
The bacterium Pseudomonas aeruginosa causes chronic respiratory infections in cystic fibrosis (CF) patients. Such infections are extremely difficult to control because the bacteria exhibit a biofilm-mode of growth, rendering P. aeruginosa resistant to antibiotics and phagocytic cells. During the course of infection, P. aeruginosa usually undergoes a phenotypic switch to a mucoid colony, which is characterized by the overproduction of the exopolysaccharide alginate. Alginate overproduction has been implicated in protecting P. aeruginosa from the harsh environment present in the CF lung, as well as facilitating its persistence as a biofilm by providing an extracellular matrix that promotes adherence. Because of its association with biofilms in CF patients, it has been assumed that alginate is also the primary exopolysaccharide expressed in biofilms of environmental nonmucoid P. aeruginosa. In this study, we examined the chemical nature of the biofilm matrix produced by wild-type and isogenic alginate biosynthetic mutants of P. aeruginosa. The results clearly indicate that alginate biosynthetic genes are not expressed and that alginate is not required during the formation of nonmucoid biofilms in two P. aeruginosa strains, PAO1 and PA14, that have traditionally been used to study biofilms. Because nonmucoid P. aeruginosa strains are the predominant environmental phenotype and are also involved in the initial colonization in CF patients, these studies have implications in understanding the early events of the infectious process in the CF airway.